Understanding the Reality of China’s Health Tourism and Consumer Demand From the Perspective of Consumers: A Cross-Sectional Study - Liu, Yao; Lin, Qian; Zhang, Dan (Frontiers in Psychology, 2022)
Background Travel for health reasons is booming around the world and in China. As a huge source and destination of health tourism, little is understood about the volume, characteristics, motivations, and preferences of health travelers in China. This study provides details of China’s health tourism reality and consumer demand of Chinese residents who did or will travel for health. Methods We established a questionnaire through literature analysis and a focus group, then collected 695 responses based on an online random sampling design. Finally, 629 questionnaires (effective recovery rate was 90%) were analyzed with statistical description, binary logistic regression, and word frequency analysis to draw the reality of health tourism, explore the influential factors, and sort out suggestions. Results In this study, 387 respondents knew of health tourism (61.53%), 446 reported interest (70.9%), and 234 had traveled for health reasons before (37.2%), with 329 occurring within China (91.4%). The top three reasons for health tourism were decompression and relaxation (116, 20%), physical examination (82, 14.1%), and health care (73, 12.6%). High costs (372, 16.3%), little disposable time (309, 13.5%), and lack of reliable professional institutions (289, 12.6%) were the main potential barriers for consumers. Professional level and quality of the institution, personal privacy, and service personnel’s attitude were the most important concerns for consumers when arranging health travel. Marital status (OR = 0.209, 95% CI = 0.085–0.514, P = 0.001) and attitude to health tourism (OR = 2.259, 95%CI = 1.553–3.287, P < 0.001) were factors for consumers’ willingness to perform health tourism. “Propaganda” was proposed most frequently by participants, followed by “service” and “price”. Conclusion The popularity of health tourists is low although there is a huge market in China. There are also differences between willingness of previous and prospective customers with varying socio-demographic characteristics in this investigation. Overall, more diverse propaganda measures should be taken, and government policies or legal documents ought to keep pace with it. Health tourism products’ promotion, as well as supporting measures and brand, need to be emphasized.